ANFIS modeling of electro-hydraulic actuator system - Ling, T. G. (IEEE, 2012)
The existence of high degree of nonlinearity in Electro-Hydraulic Actuator (EHA) has imposed a challenging work in developing a representable model for the system and controller design such that significant control performance can be achieved. The objectives of this paper are to generate an accurate EHA model using ANFIS approach and obtain a controller using Direct ANFIS Inverse approach. The ANFIS model is able to represent the nonlinear EHA system at high accuracy and low Root Mean Squared Error (RMSE). Direct ANFIS inverse controller has shown the ability in position tracking of EHA system in step and sine response. Besides, ANFIS controller is able to handle external disturbances to the system.